« L’architecte doit être le metteur en œuvre du monde » : format et métamodèle chez Peter Greenaway - Lawrence Gasquet (Interfaces)
Taking arms against Leon Battista Alberti who in 1435 argued that a window frame was an ideal metaphor to describe the world as seen by an observer, Peter Greenaway insists that his work should not be seen as « a window on the world » but as « a self-conscious and artificial construct ». Where Renaissance artists managed to produce the illusion of depth by rendering pictorial convention invisible – thanks to the universal adoption of the theory and practice of perspective – Greenaway chooses to foreground the artificial and arbitrary nature of the formats with which he works. He sees his role less as a filmmaker or visual artist than as an architect whose output is not a portrait of an external reality but the construction of a world that, while self-consciously artificial and therefore freed from dependence on the abandonment of disbelief, is capable of enveloping the viewer. Greenaway likes to say that architecture spares no one: he conceives cities as Memory Theatres which feature architecture functioning as a metamodel. For him, architecture is a symbolic construct representing the human intellect at play the world and, as such, a format that empowers mankind.